Radix Astragali Improves Dysregulated Triglyceride Metabolism and Attenuates Macrophage Infiltration in Adipose Tissue in High-Fat Diet-Induced Obese Male Rats through Activating mTORC1-PPARγ Signaling Pathway - Yang Long; Xiang-Xun Zhang; Tao Chen; Yun Gao; Hao-Ming Tian (PPAR Research)
Increased levels of free fatty acids (FFAs) and hypertriglyceridemia are important risk factors for cardiovascular disease. The effective fraction isolated from radix astragali (RA) has been reported to alleviate hypertriglyceridemia. The mechanism of this triglyceride-lowering effect of RA is unclear. Here, we tested whether activation of the mTORC1-PPARγ signaling pathway is related to the triglyceride-lowering effect of RA. High-fat diet-induced obese (DIO) rats were fed a high-fat diet (40% calories from fat) for 9-10 weeks, and 4 g/kg/d RA was administered by gavage. RA treatment resulted in decreased fasting triglyceride levels, FFA concentrations, and adipocyte size. RA treated rats showed improved triglyceride clearance and fatty acid handling after olive oil overload. RA administration could also decrease macrophage infiltration and expression of MCP-1 and TNFα, but it may also increase the expression of PPARγ in epididymal adipose tissue from RA treated rats. Consistently, expressions of PPARγ and phospho-p70S6K were increased in differentiated 3T3-L1 adipocytes treated with RA. Moreover, RA couldnot upregulate the expression of PPARγ at the presence of rapamycin. In conclusion, the mTORC1-PPARγ signaling pathway is a potential mechanism through which RA exerts beneficial effects on the disturbance of triglyceride metabolism and dysfunction of adipose tissue in DIO rats.